The Scientific Analysis of Hungarian Public Administration. New Trends and Methods. - Ádám Rixer (Central European Public Administration Review)
The purpose of this paper is to introduce those scientific methods and new paradigms that are to overcome the one-sided jurisprudential methods of analysis of public administration. On the one hand, as it has been obvious for a long time, a sort of inter- or multidisciplinary method is needed for a strong scientific and material framework which allows further conclusions. And on the other hand, beyond multi- and interdisciplinarity, it is unavoidable to reestablish the philosophic synthesis between the legal norms regulating public administration and the facts of the real operation. Probably this direction will/may be the basis and the realiser of the change of paradigm (also) in Hungarian sciences of public administration. In general it may be stated that due to the crises social sciences more and more shall start examining the real meaning of things, the broader examination frameworks of the analysed phenomena, instead of descriptive questions analysing the ways of operation. In the era of crises, when everyday experiences falsify our expectations, legal and political science become more radical: it shall examine and revise the validity of its preassumptions – which it had considered firm before.